2020
DOI: 10.3390/ijerph17010372
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Trends, and Drivers of the Utilization of Unskilled Birth Attendants during Democratic Governance in Nigeria from 1999 to 2018

Abstract: Comprehensive epidemiological data on prevalence, trends, and determinants of the use of unskilled birth attendants (traditional birth attendants (TBAs) and other unskilled birth attendants) are essential to policy decision-makers and health practitioners, to guide efforts and resource allocation. This study investigated the prevalence, trends, and drivers of the utilization of unskilled birth attendants during democratic governance in Nigeria from 1999 to 2018. The study used the Nigeria Demographic and Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 56 publications
(71 reference statements)
3
26
0
Order By: Relevance
“…Health workers' attitude in guarding their own safety may result in negative consequences such as complications during labor, including maternal or child death, depending on the stage at which a woman attends the facility. In the longer term, this may make women not to even access the facility at all and seek alternative care from other sources, such as traditional birth attendants [41], some of whom may not be skilled [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Health workers' attitude in guarding their own safety may result in negative consequences such as complications during labor, including maternal or child death, depending on the stage at which a woman attends the facility. In the longer term, this may make women not to even access the facility at all and seek alternative care from other sources, such as traditional birth attendants [41], some of whom may not be skilled [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Trained traditional birth attendants (TBAs): TBAs are community-based providers of care during pregnancy, childbirth and postnatal period without formal medical training and are traditionally independent of the health system [ 59 , 60 ]. A review on delivery by unskilled birth attendant in Nigeria revealed that the prevalence of TBA-assisted delivery remained unchanged between 1999 and 2018 [ 60 ]. Usually, the TBAs are more accessible and available within the community.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…TBAs were documented to be mainly responsible for unbooked emergencies resulting in high death rate of 2900 per 100,000 births in Zaria due to their inability to treat principal causes of maternal deaths [ 66 ]. The adverse outcomes of maternal mortality, morbidity and disability that result from delivery by TBAs occur because they are unskilled in managing pregnancy and labour complications and lack skills for risk stratification [ 60 ]. Notwithstanding, the TBAs can still contribute to the reduction of maternal morbidity and mortality by facilitating facility and skilled attended births in the community but this can only be feasible if they are appropriately integrated with the local health system.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Health workers' attitude in guarding their own safety may result in negative consequences such as complications during labor, including maternal or child death, depending on the stage at which a woman attends the facility. In the longer term, this may make women not to even access the facility at all and seek alternative care from other sources, such as traditional birth attendants [42], some of whom may not be skilled [43,44].…”
Section: Discussionmentioning
confidence: 99%